Franchisee characteristics that influence franchise business success: an analysis of focus group findings - Mohd, Zalena; Mohd Ishan, Zahira (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The franchise business is getting popularity day by day. However there is significant lacuna in understanding the crucial determinants of franchisee characteristics that influence franchise business success especially in Malaysia. Hence this study tries to identify the important factors affecting franchisee characteristics that influence the success of franchise business. An extensive focus group interview conducted to collect the data by a structured questionnaire. This research summarizes the findings of a focus group discussion, which evaluate and identify the franchisee characteristics. All focus group participants agreed and had ranked the characteristics, which had given direct impact towards determining the best criteria for the sales performance and franchisee success. Entrepreneurial capacity, professional experience, financial capacity and motivation has been ranked as an important characteristics in running franchise business. Result from this study is expected to contribute and to add on to the body of literature on the above subject matter and it can be adopted by the franchisors in determining the best candidate for the franchise business. The authors contend that this research would significantly provide a practical framework for franchisors in the selection process of franchisees.